Key role of UBQLN2 in pathogenesis of amyotrophic lateral sclerosis and frontotemporal dementia - Renaud, Laurence (Acta Neuropathol Commun, 2019)
Ubiquilin-2 (UBQLN2) is a member of the ubiquilin family, actively implicated in the degradation of misfolded and redundant proteins through the ubiquitin-proteasome system and macroautophagy. UBQLN2 received much attention after the discovery of gene mutations in amyotrophic lateral sclerosis and frontotemporal dementia (ALS/FTD). The abnormal presence of positive UBQLN2 inclusion in the cytosol of degenerating motor neurons of familial and sporadic forms of ALS patients has been newly related to neurodegeneration. Only recently, data have emerged on its role in liquid-liquid phase separation, in stress granule development and in the formation of secondary amyloid structures. Furthermore, several animal models are available to investigate its involvement in TDP-43 pathology and neuroinflammation in ALS. This review addresses the molecular pathogenetic pathways involving UBQLN2 abnormalities which are converging toward defects in clearance mechanisms. UBQLN2.